2011
DOI: 10.1007/s10443-011-9209-8
|View full text |Cite
|
Sign up to set email alerts
|

Post-Impact Mechanical Characterisation of Glass and Basalt Woven Fabric Laminates

Abstract: Two woven fabric laminates, one based on basalt fibres, the other on E-glass fibres, as a reinforcement for vinylester matrix, were compared in terms of their post-impact performance. With this aim, first the non-impacted specimens were subjected to interlaminar shear stress and flexural tests, then flexural tests were repeated on laminates impacted using a falling weight tower at three impact energies (7.5, 15 and 22.5J). Tests were monitored using acoustic emission analysis of signal distribution with load a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 21 publications
0
24
0
1
Order By: Relevance
“…In particular, it can be noticed that there is a strongly variable normalised count rate in the final part of the test when the applied stress goes beyond the quasi-elastic limit. In general, it is suggested, by comparison with what observed on pure basalt or E-glass fibre laminates in [2], that whenever the growing trend of acoustic emission is preserved (such as for example is the case for VBV laminates impacted at 15 and especially 22.5 J), damage progression which produces acoustic emission takes place preferentially in one of the two laminates. In contrast, when no clear trend is observable, it is possible that both E-glass and basalt fibre laminate forming the hybrids are damaged in a comparable way (this happen e.g., in all BVB laminates, with exception of the 22.5 J impacted ones).…”
Section: Acoustic Emission Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, it can be noticed that there is a strongly variable normalised count rate in the final part of the test when the applied stress goes beyond the quasi-elastic limit. In general, it is suggested, by comparison with what observed on pure basalt or E-glass fibre laminates in [2], that whenever the growing trend of acoustic emission is preserved (such as for example is the case for VBV laminates impacted at 15 and especially 22.5 J), damage progression which produces acoustic emission takes place preferentially in one of the two laminates. In contrast, when no clear trend is observable, it is possible that both E-glass and basalt fibre laminate forming the hybrids are damaged in a comparable way (this happen e.g., in all BVB laminates, with exception of the 22.5 J impacted ones).…”
Section: Acoustic Emission Analysismentioning
confidence: 99%
“…A previous study [2] demonstrated that non-impacted basalt fibre reinforced laminates show interlaminar shear strength and flexural properties slightly superior to those of E-glass fibre reinforced laminates. Here, in the VBV laminate, which includes the lowest number of basalt fibre layers among the three configurations, adding them does not result in an improvement of interlaminar shear strength over pure E-glass fibre reinforced laminates ( Figure 1).…”
Section: Mechanical Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies on composite structures in the past decades have shown significant benefits of woven-fabric composite materials in enhancing the impact resistance of composite structures. Most of the experimental and numerical impact analyses, however, have been focused on two-dimensional composite plates either with unidirectional or woven fabric materials [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] and little efforts are made for three-dimensional curved structures. To help contribute to a better understanding of the impact behavior of three-dimensional composite structures in general, this work provides experimental and computational drop test analyses of a woven fabric Eglass/E722 8HS composite curved beam.…”
Section: Introductionmentioning
confidence: 99%